Prevalence and predictors of overweight and obesity among adolescents in Seremban, Negeri Sembilan, Malaysia - Lai, Wai Kent; Mohd Sidik, Sherina; Lekhraj, Rampal; Gan, Wan Ying; Ismail, Siti Irma Fadhilah (Springer Science and Business Media LLC, 2022)
Introduction: Obesity is recognized as a serious public health threat. Recent evidence has warned of the alarming rise in the prevalence of childhood overweight and obesity throughout the world. This study aimed to determine the prevalence of overweight and obesity, and its associations with socio-demographic, behavioral, and psychosocial factors among school-going adolescents in Seremban, Negeri Sembilan.